Milestone moments in getting your PhD in qualitative research - Zeegers, Margaret; Barron, Deirdre (Chandos information professional series., 2015)
Milestone Moments in Getting your PhDin Qualitative Research is a guide for research students completing higher degrees with a focus on the importance of language and terminology of the theoretical and practical requirements of a given research program. The book responds to a lack of preparedness among many entrants into higher-degrees in contemporary higher education. The need among non-traditional entrants into higher-degrees for a strong background in core academic principles is made pressing due to the lack of preparation many students undergo prior to enrolment. This book might be consulted by research students as they proceed through the various milestones that may form part of a higher-degree.